Main trends of the current research of Czech paremiology - Sergienko, Olesya S. (Bohemistyka, 2019)
The main goal of this paper is to form a comprehensive bibliography of research on Czech paremiology conducted in the 21st century and to summarize the main topics of research in this field. The author outlines the main centers of Czech paremiology research and highlights the most important achievements of the modern paremiologists in Czech Republic and abroad.